Emerging strategies in colorectal cancer immunotherapy: enhancing efficacy and survival - Zhang, Yu; Guan, Haixia; Feng, Xixuan; Liu, Mengyan; Shao, Jinhuan; Liu, Mengchi; He, Jialei; Jin, Yahui; Zhu, Jinglin; Zheng, Chunli (Frontiers in Immunology, 2025)
Colorectal cancer (CRC) is a prevalent malignancy of the digestive system, with metastatic CRC (mCRC) exhibiting persistently poor overall survival rates. Consequently, there is an urgent need to develop more effective and safer therapeutic strategies. In recent years, immunotherapy has emerged as a groundbreaking approach in CRC treatment. This review highlights the advancements in immune checkpoint Inhibitors (ICIs), cancer vaccines, oncolytic virotherapy, adoptive cell therapy(ACT), and matrix-depletion therapy. Additionally, we explore potential combinatorial immunotherapy strategies for CRC, emphasizing their clinical applications and addressing the challenges associated with CRC immunotherapy. By proposing strategies to overcome these limitations, this review aims to provide novel insights into the evolving landscape of CRC immunotherapy.